Synthesis and ex vivo biodistribution of two 68Ga-labeled tetrazine tracers: Comparison of pharmacokinetics - Lambidis Elisavet; Lumén Dave; Koskipahta Elina; Imlimthan Suvachet; Lopez Brianda B.; Sánchez Ana Isabel Fraguas; Sarparanta Mirkka; Cheng R. Holland; Airaksinen Anu J. (United States, 2022)
Pretargeted PET imaging allows the use of radiotracers labeled with short-living PET radionuclides for tracing drugs with slow pharmacokinetics. Recently, especially methods based on bioorthogonal chemistry have been under intensive investigation for pretargeted PET imaging. The pharmacokinetics of the radiotracer is one of the factors that determine the success of the pretargeted strategy. Here, we report synthesis and biological evaluation of two 68Ga-labeled tetrazine (Tz)-based radiotracers, [68Ga]Ga-HBED-CC-PEG4-Tz ([68Ga]4) and [68Ga]Ga-DOTA-PEG4-Tz ([68Ga]6), aiming for development of new tracer candidates for pretargeted PET imaging based on the inverse electron demand Diels-Alder (IEDDA) ligation between a tetrazine and a strained alkene, such as trans-cyclooctene (TCO). Excellent radiochemical yield (RCY) was obtained for [68Ga]4 (RCY > 96%) and slightly lower for [68Ga]6 (RCY > 88%). Radiolabeling of HBED-CC-Tz proved to be faster and more efficient under milder conditions compared to the DOTA analogue. The two tracers exhibited excellent radiolabel stability both in vitro and in vivo. Moreover, [68Ga]4 was successfully used for radiolabeling two different TCO-functionalized nanoparticles in vitro: Hepatitis E virus nanoparticles (HEVNPs) and porous silicon nanoparticles (PSiNPs).